Hematopoietic cells and osteoblasts are derived from a common marrow progenitor after bone marrow transplantation - Dominici, Massimo (National Academy of Sciences, 2004)
Bone and bone marrow are closely aligned physiologic compartments, suggesting that these tissues may represent a single functional unit with a common bone marrow progenitor that gives rise to both osteoblasts and hematopoietic cells. Although reports of multilineage engraftment by a single marrow-derived stem cell support this idea, more recent evidence has challenged claims of stem cell transdifferentiation and therefore the existence of a multipotent hematopoietic/osteogenic progenitor cell. Using a repopulation assay in mice, we show here that gene-marked, transplantable marrow cells from the plastic-nonadherent population can generate both functional osteoblasts/osteocytes and hematopoietic cells. Fluorescent in situ hybridization for the X and Y chromosomes and karyotype analysis of cultured osteoblasts confirmed the donor origin of these cells and excluded their generation by a fusion process. Molecular analysis demonstrated a common retroviral integration site in clonogenic hematopoietic cells and osteoprogenitors from each of seven animals studied, establishing a shared clonal origin for these ostensibly independent cell types. Our findings indicate that the bone marrow contains a primitive cell able to generate both the hematopoietic and osteocytic lineages. Its isolation and characterization may suggest novel treatments for genetic bone diseases and bone injuries.